Điểu khiển mờ thích nghi các hệ thống phi tuyến thời gian rời rạc - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper present a method of designing an adaptive fuzzy controller for discrete - time nonlinear systems. The unknown nonlinear fuctions f(x), g(x) are modeled by fuzzy system f (x, θf). g (x, θg) with singleton fuzzifier, product inference engine, center average defuzzifier. The adaptation laws for the adjustable parameters θf, θg are obtained by using gradient descent algorithm or recusive least squares method.